The importance of crystal size for breathing kinetics in MIL-53(Al) - Bon, Volodymyr; Busov, Nikita; Senkovska, Irena; Boenisch, Nadine; Abylgazina, Leila; Khadiev, Azat; Novikov, Dmitri; Kaskel, Stefan (Chemical Communications, 2022)
Herein we analyze the switching kinetics of a breathing framework MIL-53(Al) with respect to different crystallite size regimes. Synchrotron time-resolved powder X-ray diffraction (PXRD) and adsorption rate analysis of n-butane physisorption at 298 K demonstrate the decisive role of crystal size affecting the time domain of breathing transitions in MIL-53(Al).
CRIS-Team Scopus Importer:2023-03-20